The Princes of Transylvania in the Thirty Years War
1 online resource
Keywords: This collection of essays presents various aspects of a group of participants in the Thirty Years War which hitherto received only cursory attention in international research context: the princes of Transylvania. Experts of the specific fields present up-to-date summaries as well as fresh results on questions of military history, diplomatic contacts, war finances, media history and discourses in political communication related to the activities of Gábor Bethlen and György Rákóczi I. Special attention is dedicated to the peculiar characteristic of the Transylvanian involvement in the great European conflict - the Ottoman threat, which derived from the fact that the principality was one of the sultan's Christian tributaries.